2020
DOI: 10.1093/botlinnean/boaa081
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of diploid and triploidAcorus calamus(Acoraceae) from southern Western Siberia, parthenocarpy in sterile plants and occurrence of aneuploidy

Abstract: Finding morphological differences between cytotypes that are stable throughout their geographical range is important for understanding evolution of polyploid complexes. The ancient monocot lineage Acorus includes two groups, of which A. calamus s.l., an important medicinal plant, is a polyploid complex with a centre of diversity in Asia. European plants are sterile triploids introduced by humans. An early study suggested that plants from temperate Asia are tetraploids, but subsequent work revealed diploids and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…Röst [10] studied leaf anatomy in four diploid, 22 triploid, and 14 tetraploid accessions of A. calamus (see [44] for a list of accessions used in [10]) and revealed that the size of air canals in leaf aerenchyma allows precise distinguishing of diploids, triploids, and tetraploids of A. calamus in a common garden experiment. Our follow-up studies [36,37] refined the protocol provided by Röst [10]. Leaf anatomy of specimens not cultivated in controlled conditions still provided information useful for inferring ploidy levels, though certain character overlapping between triploids and tetraploids was found [36,37].…”
Section: Ploidy Levelmentioning
confidence: 75%
See 4 more Smart Citations
“…Röst [10] studied leaf anatomy in four diploid, 22 triploid, and 14 tetraploid accessions of A. calamus (see [44] for a list of accessions used in [10]) and revealed that the size of air canals in leaf aerenchyma allows precise distinguishing of diploids, triploids, and tetraploids of A. calamus in a common garden experiment. Our follow-up studies [36,37] refined the protocol provided by Röst [10]. Leaf anatomy of specimens not cultivated in controlled conditions still provided information useful for inferring ploidy levels, though certain character overlapping between triploids and tetraploids was found [36,37].…”
Section: Ploidy Levelmentioning
confidence: 75%
“…Our follow-up studies [36,37] refined the protocol provided by Röst [10]. Leaf anatomy of specimens not cultivated in controlled conditions still provided information useful for inferring ploidy levels, though certain character overlapping between triploids and tetraploids was found [36,37]. Triploids, however, can be identified based on their sterility.…”
Section: Ploidy Levelmentioning
confidence: 77%
See 3 more Smart Citations